Effects of replacing fish meal with soybean meal on growth performance, feed utilization and physiological status of juvenile redlip mullet Liza haematocheila - Tao Liu; Tao Han; Jiteng Wang; Teng Liu; Pan Bian; Yuebin Wang; Xuejun Cai (Aquaculture Reports, 2021)
The purpose of this study was carried out to elucidate the effects of replacing fish meal (FM) with soybean meal (SBM) on growth performance, feed utilization, and physiological status of juvenile redlip mullet Liza haematocheila. Five test diets were formulated to replace FM protein by SBM at the levels of 0% (SBM0), 25 %(SBM25), 50 %(SBM50), 75 %(SBM75), or 100 % (SBM100). Each treatment was triplicated (20 fish per tank, initial average weight 5.08 ± 0.11 g fish−1). No significant differences were observed in weight gain (WG), feed efficiency (FE), and protein efficiency ratio (PER) between fish fed with SBM0 and SBM75 diets. However, the WG, FE, and PER values showed a decreased trend with fish fed diet containing more than 75 % SBM protein. The value of HSI decreased significantly with increasing dietary SBM levels. An increase of dietary SBM level linearly decreased energy retention (ER) and lipid retention (LR). Concentrations of serum triacylglycerol (TG) and total cholesterol (T−CHO) decreased significantly with increasing the dietary SBM levels. FM substitution with different levels of SBM had no statistical differences in the activities of trypsin, lipase (LPS), and amylase (AMS) on the intestine. Activities of superoxide dismutase (SOD), catalase (CAT), and glutamyl oxaloacetic transaminase (GOT) in the liver increased significantly with increasing dietary SBM levels. The content of malondialdehyde (MDA) in the liver was significant higher in fish fed SBM100 diet than other treatments. Based on the model of broken-line model of WG and FE, it showed that SBM can replace 51.18–52.46% FM in juvenile L. haematocheila.